2021
DOI: 10.1001/jamacardio.2020.6449
|View full text |Cite
|
Sign up to set email alerts
|

Association of Financial Hardship Because of Medical Bills With Adverse Outcomes Among Families of Children With Congenital Heart Disease

Abstract: ongenital heart disease (CHD) affects nearly 1% of US children and is associated with significant health care costs. Recurrent hospitalizations, surgical p ro c e d u re s , a n d o u t p at i e nt s e r v i c e s c re ate l a rge expenditures for families of children with CHD, even for those who have insurance, 1 and children with CHD frequently have additional comorbidities that contribute to out-of-pocket costs. 2 Indirect costs from lost wages and caregiver responsibilities further compound the financial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Having a child with CHD contributes even further to deprivation and stressors for individuals from these vulnerable communities. A recent investigation by Ludomirsky et al revealed that families experienced significant financial strain as a result of having a child with CHD ( 85 ). Data from the 2009–2010 National Survey of Children with Special Health Care Needs in the United States show that 89.1% of families with a child with CHD experienced at least one financial burden, and 14.9% of caregivers needed mental health services due to the child’s health condition ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having a child with CHD contributes even further to deprivation and stressors for individuals from these vulnerable communities. A recent investigation by Ludomirsky et al revealed that families experienced significant financial strain as a result of having a child with CHD ( 85 ). Data from the 2009–2010 National Survey of Children with Special Health Care Needs in the United States show that 89.1% of families with a child with CHD experienced at least one financial burden, and 14.9% of caregivers needed mental health services due to the child’s health condition ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lower GHI predicted lower resilience. Medical expenses for children with CHD are a common cause of financial hardship among families of children with CHD and are associated with high rates of food insecurity and delays in care for these children [ 28 ]. It is important to note that lower GHI is a factor that is difficult to modify through individual effort.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that lower GHI is a factor that is difficult to modify through individual effort. Financial hardship may elicit more stress for the parents of children with CHD [ 28 ]. Efforts to help offset medical expense-related financial burdens for low GHI parents may decrease their coping vulnerability and assure that parents are able to provide quality care for their children with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the measures of material hardship used in this study particularly reflect the context of poverty and the available measures of material hardship in the U.S. Medical hardship, for example, is unique to the United States, where, despite public insurance programs for low-income individuals, many are nevertheless unable to afford adequate health care [ 56 , 57 ]. As such, the particular degree of overlap between the domains of material hardship and their associations with child outcomes are unique to the U.S. context.…”
Section: Discussionmentioning
confidence: 99%